2022
DOI: 10.1007/s11069-022-05278-y
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for mapping of quick clay in Sweden

Abstract: Landslides may cause severe destruction that affects both the individuals and functions vital for society. Minor landslides in an area with quick clay may trigger secondary slides, influencing a much greater area compared to slides in areas with no quick clay. Today’s expanding societies demand new areas for exploitation. To effectively meet this demand, there is an increased need to identify areas where quick clay may occur. Direct or indirect methods for assessing the presence of quick clay have previously b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Previous studies at the location of the 1957 quick‐clay landslide and nearby areas alongside the Göta River have shown that different geophysical tools can successfully detect quick clays and improve the understating of their depositional environment (e.g., Dahlin et al., 2013; Malehmir, Bastani, et al., 2013; Malehmir, Saleem, et al., 2013; Pertuz & Malehmir, 2023; Salas‐Romero et al., 2019; Wang et al., 2016; With et al., 2022). Techniques, which are popular for landslide characterization (e.g.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Previous studies at the location of the 1957 quick‐clay landslide and nearby areas alongside the Göta River have shown that different geophysical tools can successfully detect quick clays and improve the understating of their depositional environment (e.g., Dahlin et al., 2013; Malehmir, Bastani, et al., 2013; Malehmir, Saleem, et al., 2013; Pertuz & Malehmir, 2023; Salas‐Romero et al., 2019; Wang et al., 2016; With et al., 2022). Techniques, which are popular for landslide characterization (e.g.…”
Section: Previous Studiesmentioning
confidence: 99%